(untitled) (INNOVATIVE ECONOMY, 2025)
Uniiat L.M., Chorna N.P., Chornyi R.S. MODERN BUSINESS MODELS OF INNOVATIVE DEVELOPMENT OF ENTERPRISES Purpose. The aim of the article is to summarize research on modern business models of innovative development of enterprises in the context of increasing globalization, digitalization and transformation of social and economic processes. Methodology of research. General scientific and special methods were used in the research process, in particular: induction and deduction - at the stage of collecting, systematizing and processing the necessary information; analysis and synthesis - when combining various components of modern business models of innovative development of enterprises; dialectical - when learning the nature, content and essence of the business model of innovative development of enterprises; monographic - when studying the scientific experience of the components of modern business models of innovative development of enterprises; abstract and logical - when forming theoretical conclusions, presenting business models of innovative development of enterprises in tabular form. Findings. A generalization of theoretical aspects of modern business models, their classification and further development and impact on the final results in a competitive environment was carried out. It was found that in a competitive environment, it is necessary to clearly organize production in accordance with the requirements of business models of innovative development of enterprises, to carry out coordinated management of them in the direction of innovative improvement of structural restructuring by introducing technological changes in management updating, preparing enterprises for activities in conditions of fierce international competition. Originality. The issue of modern business models aimed at increasing the efficiency and competitiveness of enterprises in conditions of increasing globalization, digitalization and transformation of social and economic processes has received further development. Practical value. The use of the research results will contribute to increasing the economic efficiency of economic activities of enterprises. Key words: innovations, innovative development, business models, innovative activity, competition, digitalization, management, efficiency, profitability of the enterprise.